An investigation into the spatial distribution patterns and influencing factors of fortresses in Tianshui, Gansu Province, China - Shangzhou Song; Shaohua Wang; Xiao Li; Zhengbo Wang; Liang Zhou; Cheng Su; Dachuan Xu; Jiayi Zheng; Zhuonan Huang; Haojian Liang; Junyuan Zhou (Humanities & Social Sciences Communications)
Abstract The interaction between globalization and localization profoundly influences the evolution of cultural landscapes, and the protection of local traditional culture serves as the foundation for cultural diversity and confidence. Tianshui fortresses, as typical folk defensive settlements, embody unique landscape and geographical features, reflecting distinct local cultural characteristics. This research adopts various methods, including field investigations and geographic information technologies, to explore the spatial distribution patterns of the fortresses in Tianshui and the mechanisms influencing them. It is discovered that the fortresses, as folk defensive architecture/settlements, exhibit unique geographical distribution patterns compared to state defensive buildings/settlements, characterized by relatively homogeneous specifications, formations, and distribution patterns without hierarchical differences in importance. The study finds that the reasons for fortress construction, settlement distributions, and terrain are the main factors influencing the spatial distribution of fortresses. The force transmission chain, “natural conditions—land grain productivity—land population carrying capacity—population distribution—settlement distribution—fortress distribution,” is identified as the primary mechanism affecting the spatial distribution of Tianshui fortresses. This study analyzes the distribution patterns of Tianshui fortresses, filling the gap in the specialized database on these settlements. It further deepens the theoretical understanding of the evolutionary patterns of special cultural landscapes and provides targeted reference materials for the protection of local traditional culture, heritage tourism development, and related practical applications.